Assessing the Impact of Floating Collections at the Edmonton Public Library - Ramsey, Melissa; Michas, Marta (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2026)
A “floating collection” is a popular approach to public library collection management where materials are shelved where they are returned rather than sent back to a “home” location. While it has been suggested that this approach refreshes local branch collections and reduces transit costs, it is unclear whether these benefits are realized. Concerns about this approach have also emerged as it relies on customer-initiated item movement such as holds, yet item movement resulting from holds fulfilment may exacerbate inequitable access to popular materials. In this analysis of a large and diverse urban library system, we show that floating does not appear to refresh local branch collections nor significantly impact transited materials. Our analysis also suggests that items seem to stay within a geographic area and gravitate towards branches with a higher volume of holds, meaning that items are unlikely to naturally return to branches with a lower volume of holds. Additionally, for items returned from elsewhere, a subsequent checkout at the return branch was more likely at branches with a high volume of holds.